A post-colonial instance in globalized North Malabar: is teyyam an "art form"?. Issue 4 (1st October 2020) - Pereira, Filipe; Ziganshina, Madina
Abstract: The ritual of the teyyams, in north Kerala, has been referred to as "art form, " "folk art, " "ritual art, " and such, not only by tourist guides and leaflets, but also by academic works and, more and more, in the everyday speech of local communities. 1 In this article we intend to question the adequacy of such categorizations, in light of plausible definitions of art and folklore, and investigate the motivations for such classifications, considering the correlations of social and political power in post-colonial circumstances. We defend a need for an integrated, informed and careful address to the cult of the teyyams (like any other post-colonial reality) and argue that the post-colonial discourse, despite its advantages over colonial rhetoric, can still be improved upon. It can be improved upon by acknowledging, besides the obvious consequences of the colonialist cultural and political heritage, the traces of the local, more ancient or discrete influences, interlaced with the later colonial heritage, and can provide clues for understanding of the present in its complexity. The example of the teyyams is not a random choice but rather a specific example in which the history of the relations of power, which continues from pre-colonial times, is visible on the one hand in local political discussions, and on the other hand has been fully inscribed, as tension and transgression, into the ritual in a metaphorical way.